An authentication technique on electronic performance support system (EPSS) security in a web based environment - Sunar, Mohd. Shahrizal; Bade, Abdullah (Faculty of Computer Science and Information System, 2003)
E-Learning is a form of instructional authoring that can be delivered through a CD-ROM, over the LAN or on the Internet. It includes Compute T-Based Training (CBT), Electronic Performance Support Systems (EPSS) and Web Based Training (WBT), as well as distance learning. Electronic Performance Support Systems (EPSS) represent a new paradigm in computer applications in the workplace (both academic and commercial) and are growing rapidly in importance. This growth has arisen because of the way in which such systems can be used to provide embedded training, information and advisory support at particular points of need - as and when it is required. Within many organizations EPSS has become an important mechanism for the Provision of just-in-time (JIT) training and information related to on-the-job problem solving. The provision of a performance support facility within a given task domain requires the use of appropriate prescriptive design guidelines and the application of a suitable implementation methodology. Sending a few bytes of data over a network is cheaper, faster and more convenient than sending a messenger or even making a phone call. The primary concern is security. The Internet is very public, and many people hesitate to send sensitive data over the wires where it might be intercepted by nefarious third parties. But with so many organizations excited about the benefits of e-learning, plenty of people are working on resolving the security issues. Within an EPSS, learners engage a various effectiveness that can promote meaningful learning by performing a task. EPSS include expert systems for interactive productivity software such as spreadsheets and job aids, for performing specific job tasks. The main objective of this project is to yield a software application with authentication technique capabilities and a security model in E-learning environment on Electronic Performance Support System (EPSS).